2013
DOI: 10.1159/000348290
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Glucocorticoid Receptor Protein Expression in Children with Critical Illness

Abstract: Background/Aims: The diagnostic criteria for critical illness-related corticoid insufficiency (CIRCI) are not well established, particularly for children. In addition to alterations in adrenal function, cellular resistance to glucocorticoid action could contribute to CIRCI due to alterations in the functioning of the intracellular receptor protein for corticosteroids, the glucocorticoid receptor (GR). Methods: We have therefore undertaken a pilot, prospective study to assess whether cellular GR activity can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 36 publications
4
19
0
Order By: Relevance
“…We also found higher basal and post‐ACTH salivary cortisol levels in critically ill children than in healthy controls, in accordance with published data in adults . A recent publication reported higher basal levels of salivary cortisol in children with septic shock compared with controls with congenital hypothyroidism, but concentrations of salivary cortisol were much lower in both groups compared with those found in our study . Basal salivary cortisol concentrations in our control group were similar to those previously reported for healthy children .…”
Section: Discussionsupporting
confidence: 92%
“…We also found higher basal and post‐ACTH salivary cortisol levels in critically ill children than in healthy controls, in accordance with published data in adults . A recent publication reported higher basal levels of salivary cortisol in children with septic shock compared with controls with congenital hypothyroidism, but concentrations of salivary cortisol were much lower in both groups compared with those found in our study . Basal salivary cortisol concentrations in our control group were similar to those previously reported for healthy children .…”
Section: Discussionsupporting
confidence: 92%
“…38 Another study showed that total and cytoplasmic, but not nuclear GCR levels, were significantly lower in critically ill children compared to healthy controls. 39 Other studies have also found reduced levels of GCR-α in sepsis, 40,41 while reduced GCR protein levels have been reported in various organs (liver, brain and muscle) during sepsis. 42 A link found between induction of miR124 and reduced GCR expression in septic patients 37 suggested that steroid treatment might aggravate GCR resistance in patients with high GCR-β levels, while evidence that GCR expression increased during septic shock, while GCR binding capacity decreased, proposed that it is the decreased GCR binding capacity that blocks the response to exogenous or endogenous glucocorticoids, rather than the number of receptors.…”
Section: Discussionmentioning
confidence: 93%
“…Results of these studies have shown lower GCR‐α and increased GCR‐β expression levels in septic patients compared to healthy subjects, and decreased α:β GCR ratio and increased GCR‐β expression were shown to be related to illness severity in infants with bronchiolitis . Another study showed that total and cytoplasmic, but not nuclear GCR levels, were significantly lower in critically ill children compared to healthy controls . Other studies have also found reduced levels of GCR‐α in sepsis, while reduced GCR protein levels have been reported in various organs (liver, brain and muscle) during sepsis .…”
Section: Discussionmentioning
confidence: 93%
“…Different, and probably interacting, mechanisms account for the decreased activity of glucocorticoids. Two of them are a reduction of glucocorticoid receptors [31] and an increase in the conversion of cortisol to inactive cortisone by enhanced activity of 11-β-hydroxysteroid dehydrogenase stimulated by IL-2, IL-4, and IL-13 [15]. …”
Section: Mechanism Of Circimentioning
confidence: 99%